Pengaruh Program Gerakan Literasi Sekolah dan Penggunaan Smarthphone Terhadap Minat Baca Siswa - Sri Adinda Finishi; Friyatmi Friyatmi (Universitas Negeri Padang, 2023)
This study objectives to find out the influence of school literacy movement program and smartphone use on student reading interest in SMKN 2 Padang. Sample from this study were 97 respondents who were students at SMKN 2 Padang. Based on the partial t test, it can be determined that the variable of school literacy movement and smartphone usage has a significance value of 0,000 < 0.05, The conclusion is that the variables of school literacy movement and the use of smartphones have a positive and significant influence on students' reading interests. Based on the simultaneous f test, it is obtained a significance value of 0.000 < 0.05, the conclusion of the school literacy movement program and the overall use of smartphones had a significant influence on student reading interests. The amount of influence of the independent variable on the dependent variable is 69.6%, the remaining 30.4% is influenced by variables other than the research model.